Implementation of Water Customer Information System (SIPA) at PDAM Tirta Medal City - Nurhakim, Fitra; Melati, Dea (Prodi Administrasi Publik FISIP UNPAS, 2024)
This research was conducted at the Regional Drinking Water Company (PDAM) Tirta Medal City, the purpose of this study was to determine Service Innovation at the Regional Drinking Water Company (PDAM) Tirta Medal City. This type of research is qualitative with a descriptive method. Data collection techniques by means of Interviews, Observations, and Documentation. While the research indicators are Relative advantage, Suitability, complexity, Possibility of being tried, and Ease of observation. Based on this study, it can be concluded that service innovation through the implementation of the Water Customer Information System (SIPA) Implementation at the Regional Drinking Water Company (PDAM) Tirta Medal City has been running optimally, it can be seen from its usefulness which is in accordance with the needs of PDAM employees. However, there is something that needs to be developed, namely the development of an application so that it can be used by PDAM Tirta Medal City customers.